ANALISIS HERMENEUTIK FILM TAROT - Eva Florida Simajuntak (Integrative Perspectives of Social and Science Journal, 2024)
The Tarot film is a horror film from the United States "Tarot", created by Director Spenser Cohen and Anna Halberg.  The Tarot film tells the story of a group of young people who spend the night in an old house. Well, they found a hand-painted tarot card and then tried to tell fortunes using it. Unfortunately they broke the rules of tarot reading. This rule is related to the prohibition on using other people's tarot cards.  To their horror, the broken prohibition, unbeknownst to them, has released the evil trapped in the cursed cards. One by one, they are faced with a terrible fate and must fight for survival against death.  The approach used in Tarot film analysis is a qualitative approach. Qualitative research is conducted to explain and analyze phenomena, events, social dynamics, attitudes, beliefs, and a person's or group's perception of something.  The technique used for collecting data is through the documentation method, where information is obtained from articles and journals on the Internet as well as watching Tarot films.